Respuesta :

#b

Attached

#a

  • y=x²
  • y=2(x-2)²+1

So

General equation of parabola

  • y=a(x-h)²+k

let's note the changes

  • The value of a is changed from 1 to 2 ,hence change in focus .
  • x² is turned to (x-2)² ,hence change in x axis (2 units right)
  • +1 is added hence the y coordinate of vertex goes 1 units up .
  • Vertex of first one is at (0,0) but second one is at (2,1)
Ver imagen Аноним

Answer:

Transformation of f(x) to g(x):

  • Translation of 2 units right
  • Vertical stretch by a factor of 2
  • Translation of 1 unit up

(see attachment for graphs)

Step-by-step explanation:

Translations

For a > 0

[tex]f(x+a) \implies f(x) \: \textsf{translated}\:a\:\textsf{units left}[/tex]

[tex]f(x-a) \implies f(x) \: \textsf{translated}\:a\:\textsf{units right}[/tex]

[tex]f(x)+a \implies f(x) \: \textsf{translated}\:a\:\textsf{units up}[/tex]

[tex]f(x)-a \implies f(x) \: \textsf{translated}\:a\:\textsf{units down}[/tex]

[tex]y=a\!\:f(x) \implies f(x) \: \textsf{stretched parallel to the y-axis (vertically) by a factor of}\:a[/tex]

[tex]y=f(ax) \implies f(x) \: \textsf{stretched parallel to the x-axis (horizontally) by a factor of} \: \dfrac{1}{a}[/tex]

Parent function:

[tex]f(x)=x^2[/tex]

Translated 2 units to the right:

[tex]\implies f(x-2)=(x-2)^2[/tex]

Stretched vertically by a factor of 2:

[tex]\implies 2f(x-2)=2(x-2)^2[/tex]

Translated 1 unit up:

[tex]\implies 2f(x-2)+1=2(x-2)^2+1[/tex]

Therefore, the transformation of f(x) to g(x) is:

  • Translation of 2 units right
  • Vertical stretch by a factor of 2
  • Translation of 1 unit up

Learn more about translations here:

https://brainly.com/question/27815602

Ver imagen semsee45